Using Virtual Laboratories as Interactive Textbooks: Studies on Blended Learning in Biotechnology Classrooms - Hemalatha Sasidharakurup; Rakhi Radhamani; Dhanush Kumar; Nijin Nizar; Krishnashree Achuthan; Shyam Diwakar (EAI Endorsed Transactions on e-Learning, 2015)
Virtual laboratories, an ICT-based initiative, is a new venture that is becoming more prevalent in universities for improving classroom education. With geographically remote and economically constrained institutes in India as the focus, we developed web-based virtual labs for virtualizing the wet-lab techniques and experiments with the aid of graphics favoured animations, mathematical simulators and remote triggered experimentations. In this paper, we analysed perceived usefulness of Biotechnology virtual labs amongst student groups and its role in improving the student’s performance when introduced as a learning tool in a blended classroom scenario. A pedagogical survey, via workshops and online feedback, was carried out among 600 university-level students and 100 remote users of various Indian universities. Comparing learning groups on usage of blended learning approach against a control group (traditional classroom methods) and an experimental group (teacher-mediated virtual labs), our studies indicate augmented academic performance among students in blended environments. Findings also indicated usage of remotely-triggered labs aided enhancing interaction-based lab education enabling anytime-anywhere student participation scenarios.